2018
DOI: 10.1007/s00244-018-0539-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Antiparasitic Drug Moxidectin in Cattle Dung on Zooplankton and Benthic Invertebrates and its Accumulation in a Water–Sediment System

Abstract: Two anthelmintic macrocyclic lactones-ivermectin and moxidectin-have revolutionized parasite control in cattle. These drugs are only partly metabolized by livestock, and the main route of excretion is via feces. In seasonally inundated floodplains, cattle feces come into direct contact with surface water. Important differences in pharmacokinetics and pharmacodynamics between these drugs may bear on their ecotoxicology in aquatic ecosystems. Moxidectin strongly binds to organic matter and thereby may be consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 43 publications
0
6
0
2
Order By: Relevance
“…However, moxidectin is highly toxic to aquatic organisms, such that inadvertent spillage of high volumes of product that ultimately enter waterways could have profound impacts, especially on fish. These may manifest as both acute toxicity and reproductive changes such as reduced egg hatching that could affect population dynamics in the longer term (Lumaret et al 2012;Mesa et al 2018;Muniz et al 2021). While more research into the ecotoxicological impacts of moxidectin are needed, in the short term, it would be prudent to clearly communicate to end-users that moxidectin pour-on should not be used near waterways, in volumes that inevitably lead to spillage, or during rain events that may lead to moxidectin being washed off the wombat or flooding of burrows.…”
Section: Ecotoxicity Potential With Indiscriminate Use Of Pour-on Mox...mentioning
confidence: 99%
“…However, moxidectin is highly toxic to aquatic organisms, such that inadvertent spillage of high volumes of product that ultimately enter waterways could have profound impacts, especially on fish. These may manifest as both acute toxicity and reproductive changes such as reduced egg hatching that could affect population dynamics in the longer term (Lumaret et al 2012;Mesa et al 2018;Muniz et al 2021). While more research into the ecotoxicological impacts of moxidectin are needed, in the short term, it would be prudent to clearly communicate to end-users that moxidectin pour-on should not be used near waterways, in volumes that inevitably lead to spillage, or during rain events that may lead to moxidectin being washed off the wombat or flooding of burrows.…”
Section: Ecotoxicity Potential With Indiscriminate Use Of Pour-on Mox...mentioning
confidence: 99%
“…It has been shown that MLs, including moxidectin, can be absorbed by roots, distributed in the plant, partly metabolised and cause oxidative stress [ 53 55 ]. In a greenhouse pot experiment where soil was spiked with ivermectin, this could be found in the roots and leaves of soybean plants ( Glycine max ) but not in their fruits [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The objective in this study was to use pyrantel for treatment of endoparasites, due to the widespread resistance to benzimidazoles reported in cyathostomins [8] and the documented ecotoxic effect of macrocyclic lactones [13]. Pyrantel-only treatment was not successful in reducing cyathostomin egg excretion by 85%.…”
Section: Discussionmentioning
confidence: 99%